TEACHING PRACTICE BASED ON ELEMENTS OF HIGHER-ORDER THINKING SKILLS (HOTS) BY AL-GHAZALI - Mohd Syaubari; Hashim, Abdul Talib Mohamad; Yusof, Abu Bakar; Abdullah, Zaini; Mohd Jamil, Mohd Ridhuan; Rakemi, Nik Mohd Hanis Nik; Md Zalli, Mohd Muslim (Universitas Islam Negeri Mataram, 2023)
The main objective of the study is to review relevant practices of higher-order thinking skills (HOTS) teaching according to Imam Ghazali's perspective. This study details the approach contained in the writing and interpretation by Imam Ghazali and its relationship with the concept of higher-order thinking skills (HOTS). This study is a research librarian and qualitative. Data collection methodologies used by Imam Ghazali book, especially Ihya Ulumudin, Ayuhal Walad, and Minhaj Abidin as primary and secondary sources. The process of analyzing data employee content analysis methods that have the same purpose of teaching practice based on higher-order thinking element (HOTS). The findings resulted in three main frames according to Imam Ghazali's perspective on the teaching practices based (HOTS) element. The first framework, knowledge, and understanding of the concept of the second frame are executed, and the process of how the teaching of the third frame is valuable in teaching. The unity between the three forms of income framework practicing teachers who have basic elements of higher-order thinking skills (HOTS). Overall, teachers should focus on teaching practices that formed the basis of the study of the Al-Quran to ensure delivery and practice by the students to meet the requirements prescribed by Allah and to the concept of higher-order thinking (HOTS) set up by the Ministry of Education Malaysia.